2016
DOI: 10.1016/j.cmet.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 Regulates Sweet and Alcohol Preference

Abstract: Summary Fibroblast growth factor 21 (FGF21) is a hormone induced by various metabolic stresses, including ketogenic and high carbohydrate diets, that regulates energy homeostasis. In humans, SNPs in and around the FGF21 gene have been associated with macronutrient preference, including carbohydrate, fat and protein intake. Here we show that FGF21 administration markedly reduces sweet and alcohol preference in mice, and sweet preference in cynomolgus monkeys. In mice, these effects require the FGF21 co-receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
333
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 277 publications
(371 citation statements)
references
References 29 publications
24
333
3
1
Order By: Relevance
“…For example, the allele associated with higher sugar intake, is also associated with reward-based behaviours, including higher alcohol intake. These associations are consistent with studies showing signalling effects of FGF21 to the paraventricular hypothalamus and behavioural studies in mice and non-human primates [1,2]. The FGF21 allele's association with blood pressure is not fully explained by altered alcohol intake, because the effects on blood pressure are larger than that of the KLB allele, and effects do not change when adjusting for self report alcohol intake.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…For example, the allele associated with higher sugar intake, is also associated with reward-based behaviours, including higher alcohol intake. These associations are consistent with studies showing signalling effects of FGF21 to the paraventricular hypothalamus and behavioural studies in mice and non-human primates [1,2]. The FGF21 allele's association with blood pressure is not fully explained by altered alcohol intake, because the effects on blood pressure are larger than that of the KLB allele, and effects do not change when adjusting for self report alcohol intake.…”
Section: Discussionsupporting
confidence: 77%
“…Soberg et al showed that the carbohydrate preference was specific to sugary products, and may also increase alcohol intake [13]. These findings are consistent with data from animal studies showing that FGF21 signals to reward centres in the brain [1,2]. The human genetic studies found no detectable effect on the risk of type 2 diabetes and only nominal evidence for an effect on BMI [13].…”
supporting
confidence: 79%
See 3 more Smart Citations